Stressors and the Levels of Stress Among the Undergraduate Medical, Dental and Nursing Students of a Medical College in Kathmandu - Manandhar, Seerina Adhikari; Pramanik, T (Nepal Medical College Journal, 2019)
Educational environment in medical schools is highly demanding and stressful due to various factors. The study was aimed to explore level of stress, stressors and the coping strategies among the undergraduate medical, dental and nursing students of a medical college in Kathmandu. A cross- sectional observational study was conducted among 174 consenting (95 medical, 51 dental and 28 nursing) first year undergraduate students with predesigned, pretested, semi-structured questionnaire which included socio-demographic details, Kessler psychological distress scale and Medical student stress questionnaire. Average age of students was 19.54±1.28 years. Results revealed that 66.66% of students were under stress with 25.86% having mild, 18.96% having moderate and 21.83% having severe levels of stress. Highest prevalence of stress was noted among nursing students (75.00%) with 32.14% under severe stress. Among 116 males and 58 females, males were more stressed (75.00%) than females (50.00%). Most of the students enjoyed music and chatted with their close ones to cope with stress. Academic related stressor was found to be the major stressor (2.65±0.69) with statistically significant association (p< 0.01) with the stress levels among the students. Informing students about the “must know” and “good to know” areas of the topics of every subject may be helpful to decrease the academic related stress. Regular practice of meditation, sports and cultural activities may help to reduce stress.